The First Comprehensive Investigation of the Substituent Effects of Bulky O-Alkyl or Amidoalkyl Groups in Aromatic Rings on the Domino Cyclization of Furfurylamines - Yıldırım, Ayhan; Siraj, Muhammed Aref (Synthesis, 2025)
This study represents the investigation of the impact of long alkyl or amidoalkyl groups attached to the tether moiety via the N-benzyl group on the IMDAF cyclization. We focused on investigating the sensitivity of these reactions to steric and noncovalent interactions of such groups. Although it appears to be a complex phenomenon, in the case of O-substituted salicyldehyde-based furan systems, alkyl chains, amide rotational isomerism, solvent polarity, and noncovalent interactions all contribute to the progression of the reaction. It was found that there was no significant angle compression with the elongation of the O-alkyl groups. Therefore, contrary to expectations, significant decreases in yields were observed as the hydrocarbon chain lengthened. This demonstrates that these flexible groups can be pivotal in the reaction, influencing the nature of the transition state. Alkyl groups exert no influence on the stereochemistry of the cycloaddition and solely the exo product is formed. In general, cycloaddition is influenced by the solvent’s polarity, and at low temperatures, the nonpolar solvent is more effective.
Keywords: IMDAF reactions; Noncovalent interactions; Steric effects; Epoxyisoindole-7-carboxylic acids; γ-Lactams